Scalar Particles Tunneling Radiation in the Demianski-Newman Spacetime with Influences of Quantum Gravity - Zhonghua Li (Advances in High Energy Physics)
In this paper, using Hamilton-Jacobi ansatz, we investigate scalar particle tunneling radiation in the Demianski-Newman spacetime. We get the effective temperature with influences of quantum gravity and compare this temperature with the original temperature of the Demianski-Newman black hole. We find that it is similar to the case of fermions; for scalar particles, the influence of quantum gravity will also slow down the increase of Hawking temperatures, which naturally leads to remnants left in the evaporation.